Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1515/lpts-2016-0023
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Nanotechnologies and Advanced Materials Industry in Science and Entrepreneurship: Socioeconomic and Technical Indicators. A Case Study of Latvia (Part One)

Abstract: The present scientific paper is the first part of two publications, where the authors obtain results from the scientific research presented in a series of works on the development of the nanotechnologies and advanced materials industry in science and entrepreneurship in Latvia. The study has a focus on finding proper socioeconomic and technical indicators. It provides resume on a scope of the study. The paper contains the developed structure of engineering economic indicator system, determined groups of indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In accordance with the above-mentioned topicality and the continuation of the present study, which follows and correlates with the in-depth analysis of the previous two studies [2], [3], the development of the nano-field can also be identified and revealed from the perspective of scientific indicators. With regard to the structure of the research on nanotechnologies and advanced materials industry in science and entrepreneurship, it should be noted that the research will reveal crucial scientific indicators of the development of the nano-field at the macro, micro, and meso development levels of economic environment in Latvia.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with the above-mentioned topicality and the continuation of the present study, which follows and correlates with the in-depth analysis of the previous two studies [2], [3], the development of the nano-field can also be identified and revealed from the perspective of scientific indicators. With regard to the structure of the research on nanotechnologies and advanced materials industry in science and entrepreneurship, it should be noted that the research will reveal crucial scientific indicators of the development of the nano-field at the macro, micro, and meso development levels of economic environment in Latvia.…”
Section: Introductionsupporting
confidence: 89%
“…Referring to the previous research on scientific indicators at all levels, it can be concluded that the indicators characterising the development of scientific research are closely related to the amount of funding allocated to the research activity (see assessment in the group of economic indicators [2]) and the number of people employed in science. Although the scientific development indicators of Latvia in comparison with other countries of the world are average, the performance of scientific development indicators actually corresponds to the amount of financing invested in science and even would be higher if public funding in R&D were at the level of developed countries of the EU.…”
Section: Assessment Of the Scientific Indicatorsmentioning
confidence: 99%